2016
DOI: 10.1590/1809-4392201501284
|View full text |Cite
|
Sign up to set email alerts
|

Hematological responses of tambaqui Colossoma macropomum (Serrassalmidae) fed with diets supplemented with essential oil from Mentha piperita (Lamiaceae) and challenged with Aeromonas hydrophila

Abstract: In fish farmings, diseases can be reduced by using immunostimulants. The aim of this study was to evaluate the immunostimulant potential of Mentha piperita in tambaqui fed with 0, 0.5, 1.0 and 1.5% of oil per kg of commercial fish feed. The fish were inoculated with Aeromonas hydrophila to challenge them. Hematological and biochemical parameters were determined after 30 days of feeding and seven days after the challenge. There was no mortality and M. piperita oil did not influence fish production parameters. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…Immunostimulants have the potential to improve the function of head kidney meanwhile augmenting the erythropoiesis and haematosynthesis. This in turn can influence the haematological status of fish as observed in different studies (Prabu et al 2016;Ribeiro et al 2016). The present study also revealed positive effect of dietary fucoidan on the RBC count and haemoglobin content.…”
Section: Discussionsupporting
confidence: 84%
“…Immunostimulants have the potential to improve the function of head kidney meanwhile augmenting the erythropoiesis and haematosynthesis. This in turn can influence the haematological status of fish as observed in different studies (Prabu et al 2016;Ribeiro et al 2016). The present study also revealed positive effect of dietary fucoidan on the RBC count and haemoglobin content.…”
Section: Discussionsupporting
confidence: 84%
“…Many researchers have conducted their studies to explore the benefits of EOs as dietary additives on fish (see Table 1) and other animal species (Benchaar et al 2008;Brenes & Roura 2010;Zeng et al 2015). Different methods of adding the EOs to fish diets are reported in the literature such as mixing the EOs with an organic diluent (Dairiki et al 2013;Ribeiro et al 2016;Brum et al 2017), phosphate-buffered saline (PBS) (Navarrete et al 2010) or incorporation with some ingredients of the diet, such as defatted rice bran (Zheng et al 2009). In most of the recent studies using natural EOs in fish diets (Saccol et al 2013;Volpatti et al 2013;Ferreira et al 2014;Souza et al 2015;Diler et al 2016;Hassaan & Soltan 2016;Sutili et al 2016;Zeppenfeld et al 2016a,b), the EOs are generally used as a blend with a carrier oil or combined with other oils in the feed, commonly the lipidic fraction of the diet (i.e.…”
Section: Stability In Feedmentioning
confidence: 99%
“…However, after challenge with A. hydrophila, the total leukocytes and lymphocytes number decreased among the fish fed on diets containing the essential oil of M. piperita, probably due to migration of these cells to the tissues. The increased leukocytes and erythrocytes number may be attributed to the effective antioxidant role of 1.0% of the essential oil from M. piperita (Ribeiro et al, 2016), that was related by Giri et al (2017) when applied H. enneraspermus in L. rohita.…”
Section: Tablementioning
confidence: 97%
“…In addition, the most of these chemical products are toxic and compromise the gills, integument and liver, and also are potential pollutants of the environment and may cause risks to human health (Malheiros et al, 2016). However, herbal substances have several advantages, such as reduced environmental impact, biodegradability, lower residue levels in fish and low toxicity, resulting in low likelihood of causing resistance and low cost for farmers (Ribeiro et al, 2016;Hashimoto et al, 2016).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation